2
$\begingroup$

I'm self studying from a Classical Introduction to Modern Number Theory by Ireleand and Rosen. In the exercises for the chapter on Gauss and Jacobi sums I came across this question.

Let $\chi$ be a non-trivial multiplicative character of $F_p$ and let $\rho$ be the character of order 2 (the legendre symbol), then if $k \in F_p$ and $k \neq 0$, then $\sum_{t=0}^{p-1} \chi (t(k-t)) = \chi(k^2/4)J(\chi,\rho)$.

Now, $\sum_{t=0}^{p-1} \chi(t(k-t)) = \sum_{c=0}^{p-1}N(t(k-t)=c)\chi(c)$, where $N(t(k-t)=c)$ is the number of solutions to the equations $t(k-t) = c$. Now, $t(k-t) = c$ is solveable iff its discriminant is a quadratic residue and if its solveable there are two solutions. So $N(t(k-t) = c) = N(s^2 = k^2 - 4c) = 1 + \rho(k^2-4c)$

So, the sum becomes $\sum_{c=0}^{p-1}(1 + \rho(k^2-4c))\chi(c) = \sum_{c=0}^{p-1}\rho(4)\rho(k^2/4 -c)\chi(c) = \sum_{c=0}^{p-1}\rho(c)\chi(k^2/4 - c)$

Now, $\chi(k^2/4)J(\chi,\rho) = \chi(k^2/4)\sum_{t=0}^{p-1}\chi(t)\rho(1-t)$

And no matter how I try to manipulate it, I can't get the equations to equal each other. Did I do something wrong along the way?

$\endgroup$
2
$\begingroup$

In $\sum_{c=0}^{p-1}(1 + \rho(k^2-4c))\chi(c)$,

try replacing $c$ with $k^2/4c$ instead of $k^2/4-c$. (To get to the right hand side you want to be able to pull out a $\chi(k^2/4)$, so put yourself in a position to do this.) This should take you to

$\chi(k^2/4)\sum_{t=0}^{p-1}\chi(t)\rho(1-t)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.